Optimization of OLED - Wong, Joel Chee Wei (Nanyang Technological University, 2021)
Organic light emitting diode (OLEDs) with the advantages of high efficiency, lower power consumption, flexible, transparent, and lightweight, enabling it to be widely used in lighting and display technologies such as mobile phones and television. In this report, the operations characterization of OLEDs was studied. Through simulation, various thickness of the OLED layers, more specifically the hole and electron transport layers, and the emission layer will be used to simulate the efficiency of the OLED before combining and optimizing the structure of OLEDs based on the simulation results.